2003
DOI: 10.1093/fampra/cmg504
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the smoking behaviour and attitudes of smokers who believe they have smoking-related problems with those who do not

Abstract: Smokers who attend GPs' routine consultations and believe that they have smoking-related problems are more motivated to stop than others. This suggests that it is important for GPs to ascertain patients' views about the aetiology of their symptoms before discussing smoking with them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…17 More directly relevant, a survey of smokers conducted after a consultation with their GP found that 25% intended to quit within one month, 11 rising to 37% of those who considered they had a smoking related problem. 18 In the present study over 80% of untreated smokers had consulted their GP during the two year study period, with over a quarter consulting more than 10 times, indicating that there are missed opportunities for prescribing smoking cessation treatments. About three times as many smokers received a prescription for NRT than bupropion, suggesting the former is first line treatment for motivated smokers.…”
Section: Discussionmentioning
confidence: 49%
“…17 More directly relevant, a survey of smokers conducted after a consultation with their GP found that 25% intended to quit within one month, 11 rising to 37% of those who considered they had a smoking related problem. 18 In the present study over 80% of untreated smokers had consulted their GP during the two year study period, with over a quarter consulting more than 10 times, indicating that there are missed opportunities for prescribing smoking cessation treatments. About three times as many smokers received a prescription for NRT than bupropion, suggesting the former is first line treatment for motivated smokers.…”
Section: Discussionmentioning
confidence: 49%
“…8 Smokers who believe that they have a smoking-related disease 9 and attribute their symptoms to smoking 10 are more motivated to quit. In addition, smokers who have experienced and attributed an acute sentinel health event to smoking were more likely to stop smoking compared with community-based estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Attenuated concerns may refl ect masked symptoms due to use of menthol cigarettes ( Garten & Falkner, 2003 ) or other health priorities or concerns. Research among White smokers suggests that smokers who believe their symptoms are smoking related are more motivated to quit than are those who do not ( Coleman, Barrett, Wynn, & Wilson, 2003 ). Thus, interventions designed for Black smokers might emphasize early physical symptoms to increase readiness to quit smoking ( Prokhorov et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%